Inkspell / 2. - Funke, Cornelia, 1958- (Inkheart Trilogy, 2007)
When Dustfinger finds a crooked storyteller who can read him back to Inkscape, he leaves his apprentice Farid behind; but Farid seeks out Meggie and the two follow him back into the enchanted book.